Perceptions of teacher training and possible links with the teaching of mathematics: a case study . - Moreira Mora, Tania Elena (2011)
This article reports preliminary findings from a study of the perceptions of secondary school teachers, about their training in the field of mathematics and its possible link with the joint methodological and the attitude of the students towards the subject in the Huetar educational Atlantic regionduring the year 1996.We conducted a case study with the five teacherswho completed their training in the Regular Plan of the University of Costa Rica, at the regional headquarters of Limon. This plan was initiated in 1992 with a duration of three years and was awarded the degree of faculty.